Ethiopia Alive & Thrive Endline Survey 2014: Supervisors of Health Extension Workers - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the supervisors of health extension workers survey that was conducted to gather data for the endline part of the impact evaluation of the Alive & Thrive (A&T) interventions in Ethiopia. The broad objective of the impact evaluation in Ethiopia is to measure the impact of A&T’s community-based interventions (CBI), delivered through the government's health extension program (HEP) platform, in the reduction of stunting and improvement of infant and young child feeding (IYCF) practices in two regions where the integrated family health program (IFHP) operates, namely Tigray and SNNPR (Southern Nations, Nationalities, and People’s Region). A&T is a six-year initiative funded by the Bill & Melinda Gates Foundation to facilitate change for improved infant and young child feeding (IYCF) practices at scale in Bangladesh, Ethiopia, and Viet Nam. The goal of A&T is to reduce avoidable death and disability due to suboptimal IYCF in the developing world by increasing exclusive breastfeeding (EBF) until 6 months of age and reducing stunting of children 0-24 months of age. The impact evaluation of the A&T Ethiopia community-based intervention and mass media activities includes the 2010 baseline and 2014 endline surveys and a smaller-scale 2013 process evaluation survey. Together, these studies generate answers to one of the major learning objectives for the overall initiative: how A&T interventions achieve their impact. The Ethiopia endline survey applied five separate questionnaires that aimed to capture elements along the program impact pathways. These instruments included a household questionnaire, a community questionnaire and 3 frontline health workers questionnaires, which are: - health extension workers (HEW) questionnaire - supervisors of HEWs questionnaire - volunteer community health promoters questionnaire The supervisors of HEWs questionnaire, along with the other two FLW questionnaires, aimed at assessing four major issues: (1) frequency of interactions between FLWs and mothers/caregivers and modes of interactions; (2) content of the interactions between FLWs and mothers/caregivers, especially discussions about IYCF messages and the time spent on IYCF-related discussions; (3) IYCF knowledge and training received by FLWs; and (4) FLWs’ motivation and satisfaction about their jobs. These are captured by questions on perceptions related to workload and level of job satisfaction. The roles of supervisors are somewhat different from the other two types of FLWs. They do not come in direct contact with caregivers, yet they are mainly responsible for providing training and supervision to HEWs, and monitoring and supervising the training of volunteers conducted by HEWs. The questionnaires for supervisors, therefore, aim at capturing these interactions. Together, combining information from the HEW and HDA/WDA questionnaires with those administered to supervisors will generate valuable data about the organizational context for FLWs.